INTERNALISASI PENDIDIKAN AGAMA ISLAM DALAM MENGATASI ANAK PUTUS SEKOLAH - Hirzulloh, Muhammad Faiq (PKBM DAARUL AHKAAM, 2024)
Nowadays, there are a lot of teenage problems such as drugs, drunkenness and free sex that occur in the younger generation. Basically, those who are still in school will be easier to direct, because they get religious education and character education. Unlike children who drop out of school. This is where the role of Islamic religious education is very important as a problem solver for those who are forced to drop out of school. Internalization of Islamic religious education also needs to be applied to overcome children who drop out of school, especially their mentality. Moreover, they have great potential to experience mental decline problems. This research is a literature study The subjects in this study are books written by Dr. Sarwo Edy MM, Sumarta, S.Pd.I, M.Si and KRAT. Ir. H. Mardiyana, MM.Ph.DS. entitled The Urgency of Islamic Religious Education in Mental Development and Character Building of Children's Personality: Theoretical and Practical Studies. Furthermore, secondary data is a literature study related to the internalization of Islamic religious education in overcoming school dropouts. The result of the research is that Islamic religious education plays a role as a problem solver for school dropouts. In the problem of school dropouts, Islamic religious education needs to be internalized when the child's mentality drops and cannot accept reality. In the process of internalizing Islamic religious education in overcoming school dropouts, there are several ways that can be done. First, the method of education by example. Second, the method of education by habituation, third, the method of education by advice. Fourth, educational methods with supervision and fifth, educational methods with punishment.